IMPLEMENTASI PERATURAN DAERAH PROVINSI JAWA BARAT NO. 1 TAHUN 2021 TENTANG FASILITAS PENYELENGGARA PONDOK PESANTREN DITINJAU DARI PERSPEKTIF SIYASAH DUSTURIYYAH: (Studi Komparatif Kebijakan Publik Di Pondok Pesantren Sulalatul Huda dan Pondok Pesantren Al-Mubarok Kota Tasikmalaya) - Muhammad Ibdan Ruhdinuloh; Ecep Nurjamal; Asep A. Arsyul Munir; nurjamal, ecep (Program Studi Hukum Tata Negara, 2024)
The background to this study is the perception that the regional regulations in question may be populist in nature, in the sense that they have political elements, and their implementation in the relevant research location has not been optimal. Data for this research was collected through observation, interviews and literature review. The aim of this study is to evaluate the implementation of West Java Provincial Regulation No.1 of 2021 on Facilitating the Management of Boarding Schools from the perspective of Siyasah Dusturiyah (Comparative Study of Public Policy in Sulalatul Huda and Al-Mubarok Boarding Schools). Its focus is on providing clear, concise, and objective information, with a logical progression of ideas and a causal connection between statements. Technical terms are adequately explained, and conventional academic structures are followed. There is a consistent use of formal language, passive tone, and precise vocabulary throughout the document. The text is free from grammatical, punctuation, and spelling errors, and references are cited and formatted consistently. Bias is avoided by utilizing hedging techniques. The study employs a descriptive qualitative research approach. The research findings suggest that the implementation of the Regional Regulation No.1 Year 2021, which facilitates the operation of Islamic boarding schools in West Java, has been achieved from the perspective of Siyasah Dusturiyyah. However, the execution has not been fully optimised, especially at Sulalatul Huda Islamic Boarding School. On the other hand, in Al-Mubarok Islamic Boarding School - the benchmark for this study - the implementation of the regulation appears to have been relatively maximised. This is evidenced by the numerous achievements of the Pesantren on a local and national level, the objectively excellent condition of the Pesantren, as well as the empowerment, development, recognition, and affirmation that have been successfully implemented in accordance with the relevant regional regulations, although not all of them have been fully realized by the government agencies.